Review of Adsorption of Fe Metal by Activated Carbon Adsorbent - Fakta Ideal Zega; Rini Selly; Moondra Zubir (Indonesian Journal of Chemical Science and Technology (IJCST), 2021)
Many researchers have used activated carbon as adsorbents for the adsorption heavy metal. The aim of present study was to investigate the adsorption properties of activated carbon for the removal of Fe metal. A research has been conducted to determine optimal of stirring time, stirring speed, adsorbent mass and particle size on activated carbon adsorbent in adsorption Fe metal. From the literature survey that increase in stirring time, stirring speed and adsorbent mass enhancing the removal of Fe metal. The results show which is on stirring time 60 minutes, stirring speed 90 radians per minute and adsorbent mass 2 grams have a high adsorption of the heavy metals of iron. Whereas the smaller of particle size enhancing the adsorption of Fe metal. The particle size of 200 mesh is the optimal particle size for adsorption of Fe. Finally, activated carbon showed to be a good potential adsorbent for removing Fe.